Balanced performance and structural mechanisms in industrial product design systems (Al-Academy, 2018)
The research focused on (balanced performance and structural mechanisms in industrial product design systems) by focusing on product development in a manner that is able to meet the human requirements through the effect of smart technology on the systems of product designs and its effectiveness in achieving the design and functional variables that have an effective effect in User and industrial products, correspond to the requirements of the user life at the level of daily interaction. The first chapter ensures the problem of research is the following question: What are the mechanisms to achieve balanced performance in some systems design to fit with the variables B N User and industrial products? The objective of the research was to identify the mechanisms of balanced performance in the design systems of industrial products and the extent of their interaction with the user. The limits of this study included electronic electrical appliances products for Brother, MICOM and L.G manufactured in 2015-2016. The second chapter contains the axes of the theoretical framework. The third chapter included the research procedures of the study society. While the fourth chapter contains the findings and conclusions reached by the researcher. The most important results were as follows:- The sample of the search for the achievement of balanced performance on the performance level resulted from the adequacy of models in the performance of tasks, and to achieve the functions desired, which in turn created a kind of interactive interaction and cultural communication, social and behavioral.The most important conclusions in the research:- The formal formative variables expressed by the mechanism of symbols and signals of the latent functional system are verified with the suitability of the use, which is based on several methodological and technical data, to show the sample models with a relative balance in the formality and clarity with the user.